2017
DOI: 10.1039/c7tc02076g
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically manipulated lasing enabled by a reconfigured fingerprint texture of a cholesteric self-organized superstructure

Abstract: Laser emission based on an electrically reconfigured fingerprint texture of a cholesteric liquid crystal helical superstructure is achieved by judiciously designing the composition of the device material and the device structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…As we mentioned above, QDs are semiconductor nanoparticles with unique physical characteristics such as high quantum yields, large absorption cross-section, tunability of fluorescence emission, excellent colour purity, broad excitation spectra, good stability and long Light-driven phase transitions in LCs are a fascinating topic from both the scientific and the technological point of view. Apart from the photothermal effect [289], such phase transition can also be obtained by the photoisomerization ability of azo benzene dyes [290][291][292][293][294], which, at the same time, is also usually used for fabricating LC lasers [32,[295][296][297][298]. However, because these dyes are not nanoparticles, they will not be discussed within the framework of this review.…”
Section: Photonic Applicationsmentioning
confidence: 99%
“…As we mentioned above, QDs are semiconductor nanoparticles with unique physical characteristics such as high quantum yields, large absorption cross-section, tunability of fluorescence emission, excellent colour purity, broad excitation spectra, good stability and long Light-driven phase transitions in LCs are a fascinating topic from both the scientific and the technological point of view. Apart from the photothermal effect [289], such phase transition can also be obtained by the photoisomerization ability of azo benzene dyes [290][291][292][293][294], which, at the same time, is also usually used for fabricating LC lasers [32,[295][296][297][298]. However, because these dyes are not nanoparticles, they will not be discussed within the framework of this review.…”
Section: Photonic Applicationsmentioning
confidence: 99%
“…Strangi et al demonstrated thermally controllable lasing wavelength and electrically controllable emission intensity in CLC laser arrays fabricated by confining the CLC in holographically patterned polymer microchannels . Recently, lasing in the fingerprint texture of CLCs has been demonstrated where the laser emission direction can be switched between two orthogonal directions . The emission wavelength and lasing mode can be manipulated with a comparatively low external electric stimulation.…”
Section: Uniform Lying Helix Structurementioning
confidence: 99%
“…[100,201,[205][206][207][208][209][210][211][212] These controllable actions enable CLCs to be used in ground-breaking devices and application. This is because they possess a self-organized helical structure that can be controlled and switched by many stimuli.…”
Section: Cholesteric Lcsmentioning
confidence: 99%
“…This is because they possess a self-organized helical structure that can be controlled and switched by many stimuli. [100,201,[205][206][207][208][209][210][211][212] These controllable actions enable CLCs to be used in ground-breaking devices and application. In general, most of the applications come from the fact that external stimuli cause pitch changes [213][214][215][216][217] and helical axis switching, [33,35] both resulting in remarkable mesoscopic changes that qualify incredible well as diffraction gratings.…”
Section: Cholesteric Lcsmentioning
confidence: 99%